Diffraction, fourier optics, and imaging - Ersoy, Okan K. (Hoboken, N.J. : Wiley, 2007)
This book presents current theories of diffraction, imaging, and related topics based on Fourier analysis and synthesis techniques, which are essential for understanding, analyzing, and synthesizing modern imaging, optical communications and networking, as well as micro/nano systems. Applications covered include tomography; magnetic resonance imaging; synthetic aperture radar (SAR) and interferometric SAR; optical communications and networking devices; computer-generated holograms and analog holograms; and wireless systems using EM waves.
Keywords: Optics & Photonics; Photonics & Lasers; Electronic books